Debating the Legal Status of the Ornaments Rubric: Ritualism and Royal Commissions in Late Nineteenth- and Early Twentieth-Century England - Cruickshank, Dan D. (Studies in church history, 2020)
This article uses the history of the Ornaments Rubric in the late nineteenth and early twentieth century to explore the emergence of claims to self-governance within the Church of England in this period and the attempts by parliament to examine how independent the legal system of the church was from the secular state. First, it gives an overview of the history of the Ornaments Rubric in the various editions of the Book of Common Prayer and the Acts of Uniformity, presenting the legal uncertainty left by centuries of Prayer Book revision. It then explores how the Royal Commission into Ritualism (1867-70) and the Public Worship Regulation Act (1874) attempted to control Ritualist interpretations of the Ornaments Rubric through secular courts. Examining the failure of these attempts, it looks towards the Royal Commission on Ecclesiastical Discipline (1904-6). Through the evidence given to the commission, it shows how the previous royal commission and the work of parliament and the courts had failed to stop the continuation of Ritualist belief in the church's independence from secular courts. Using the report of the royal commission, it shows how the commissioners attempted to build a via media between strict spiritual independence and complete parliamentary oversight.